Suitability of circulating miRNAs as potential prognostic markers in colorectal cancer - Ristau, Jonas; Gigić, Biljana; Hoffmeister, Michael; Brenner, Hermann; Ulrich, Alexis; Schneider, Martin; Ulrich, Cornelia; Habermann, Nina (Cancer epidemiology, biomarkers & prevention, 2014)
miRNAs are crucial in cellular processes and have been shown to be abnormally expressed in cancer tissue and the circulation. Circulating miRNAs may serve as a novel class of minimally invasive biomarkers for prognosis. Within a first methodologic study, we evaluated the miRNA profile kinetics in the plasma of patients with colorectal cancer after surgical tumor removal to identify potential suitability as prognostic biomarkers. This pilot study is based on the ColoCare Study, a cohort study of newly diagnosed patients with stage I-IV colorectal cancer. Colorectal cancer pre- and postsurgical blood (2-7 days after surgery) and 6 months follow-up blood from 35 patients were examined and candidate miRNAs were investigated in the plasma. miRNA levels were measured by two-step qRT-PCR. Statistical analysis was performed using log-transformed normalized CT values using SAS 9.3. Comparing pre- and postsurgical miRNA levels revealed a statistically significant decrease of nine circulating miRNAs after surgery (miR92a, miR18a, miR320a, miR106a, miR16-2, miR20a, miR223, miR17, and miR143). Analyses of plasma levels over all three time points demonstrated a statistically significant decrease from presurgery to postsurgery and re-increase from postsurgery to the six months follow-up time point of four circulating miRNAs (miR92a, miR320a, miR106a, and miR18a). We were able to show for the first time that in plasma miRNA profiles change within days after colorectal cancer surgery. Our results underscore the role of the investigated miRNAs in colorectal cancer and their potential utility as prognostic biomarkers.
Gesehen am 05.11.2020
Name "Herrmann Brenner" ist in der Verfasserangabe falsch geschrieben